How do Coastal High School Students Perceive Student-centred Learning Approach? - Agust Satria; Siregar Eko Febri Syahputra; Hindrasti Nur Eka Kusuma; Malik Abdul; Rahmatina Desi; YulitaÇ Inelda; Demir Çağlar; Khofifah Khofifah; Aminingsih Aminingsih; Irawati Irawati; Hafizah Nurul; Noviani Raja; et al. (BIO Web of Conferences)
This study explores the perceptions of coastal high school students regarding the student-centred learning approach, which prioritizes student autonomy and active engagement. The research specifically focused on Junior High School Number 10 in Tanjungpinang, Riau Islands Province, to understand how geographic and socioeconomic factors influence these students’ educational experiences. Utilizing a descriptive quantitative research design, data were collected through structured questionnaires, followed by analysis using the Rasch Model. This study investigates how coastal high school students view student-centred learning, highlighting the benefits to participation and academic performance in particular. However, certain noteworthy obstacles were noted, including the scarcity of technology and the difficulty of adjusting to more autonomous learning environments. Solutions like improved technology infrastructure and focused teacher preparation are proposed to address these problems. These results highlight how crucial it is to offer customized educational support in coastal areas in order to maximize the efficacy of student-centred pedagogies.